2013
DOI: 10.1021/jf305213e
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Antioxidant Activity of Procyanidin Extracts from the Pericarp of Litchi chinensis Processing Waste by Two Probiotic Bacteria Bioconversions

Abstract: Litchi chinensis pericarp from litchi processing waste is an important plant source of A-type procyanidins, which were considered a natural dietary supplement because of their high biological activity in vivo. Litchi pericarp oligomeric procyanidins (LPOPCs) did not selectively modify the growth of Streptococcus thermophilus and Lactobacillus casei -01 at concentrations of 0.25 and 0.5 mg/mL, and it was demonstrated that the two strains could transform procyanidins during their log period of growth by two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 33 publications
4
32
0
Order By: Relevance
“…A recent study evaluated the ability of probiotic bacteria to convert procyanidins in vitro. The author found that the 3‐(4′‐hydroxyphenyl)propionic acid derived from epicatechin and A2 was much higher than that from Litchi pericarp oligomeric procyanidins, indicating that it was easier for Lactobacillus to transform the procyanidins with a lower degree of polymerization . Another study using a pig cecum model showed similar phenomena in which only 40% of A‐type trimmers were degraded within 8 h of incubation compared to 80% of A‐type dimers .…”
Section: Resultsmentioning
confidence: 96%
“…A recent study evaluated the ability of probiotic bacteria to convert procyanidins in vitro. The author found that the 3‐(4′‐hydroxyphenyl)propionic acid derived from epicatechin and A2 was much higher than that from Litchi pericarp oligomeric procyanidins, indicating that it was easier for Lactobacillus to transform the procyanidins with a lower degree of polymerization . Another study using a pig cecum model showed similar phenomena in which only 40% of A‐type trimmers were degraded within 8 h of incubation compared to 80% of A‐type dimers .…”
Section: Resultsmentioning
confidence: 96%
“…Given that, it is less likely that our probiotic strain (L. casei 01), with apparently lower antioxidant potential compared to the other strains of L. casei species, could exert its full effects. Li et al showed in an in vitro study that L. casei 01 could convert procyanidins to more effective antioxidant products [50]; thus, it is probable that consuming probiotic foods that are also rich in antioxidants is more effective than taking probiotic supplements in reducing oxidative stress indices. L. casei 01 has been shown to sufficiently resist gastric and intestinal pH and properly adhere to IEC-6 epithelial cells (which is an in vitro indicator of proper colonization in the gut) [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Two probiotics, Streptococcus thermophilus and Lactobacillus casei-01 were able to metabolize A-type procyanidins from Litchi pericarp during their log phase of growth. S. thermophilus transformed procyanidin A2 to its isomer and Lactobacillus casei-01 decomposed flavan-3-ols into 3,4-hydroxyphenylacetic acid, 4-hydroxyphenylpropionic acid, m-coumaric acid, and p-coumaric acid (Li et al, 2013). Aspergillus fumigatus was able to grow on purified B-type procyanidins from apples.…”
Section: Microbial Metabolism Of Proanthocyanidinsmentioning
confidence: 99%